Pharmacokinetics and Pharmacodynamics of Cenerimod, A Selective S1P1R Modulator, Are Not Affected by Ethnicity in Healthy Asian and White Subjects - Pierre‐Eric Juif; Jasper Dingemanse; Peter Winkle; Mike Ufer (Wiley, 2021)
Cenerimod is a sphingosine‐1‐phosphate 1 receptor (S1P1R) modulator in phase II development for treatment of systemic lupus erythematosus. Its pharmacokinetics (PKs), pharmacodynamics (PDs), as well as safety and tolerability were investigated in white and Asian subjects to allow for recruitment of Asian patients in future studies. A randomized, double‐blind, placebo‐controlled parallel‐group study was performed in 20 healthy male subjects (n = 10 per ethnicity). A single, oral dose of 4 mg cenerimod or placebo (ratio 8:2) was administered under fasted conditions. The PKs of cenerimod were similar in white and Asian subjects indicated by geometric mean ratios (90% confidence interval) of 0.99 (0.80-1.21) for maximum plasma concentration, 0.96 (0.75-1.24) for area under the plasma concentration‐time curve from 0 to infinity, and 1.04 (0.86-1.25) for terminal half‐life. Accordingly, the extent and time course of reduction in lymphocyte count (as PD biomarker) were also similar in white and Asian subjects as compared with placebo. As observed for other S1PR modulators, a transient mean (SD) heart rate reduction in white (15.1 (14.8) bpm) and Asian (11.8 (6.16) bpm) subjects was observed following administration of cenerimod. The drug was safe and well‐tolerated indicated by occurrence of a single adverse event of chemical conjunctivitis in a white subject that was not suspected as study drug related. In conclusion, the determined absence of any relevant PK or PD differences supports using the same doses of cenerimod in white and Asian patients in upcoming late‐phase studies.